Determining Factors Associated With The Knowledge, Attitude And Practice Of Covid-19 Pandemic Among Medical Students In Malaysia - Amirah Azzeri; Muhammad Amalin; Kamaruddin Ezieyan; Zaidi Nurin; Nazri Aina; Ridza Anis; Anuar Balkhis; Affandi Arni; Zuhairi Alia; Rashid Farhan; Ayub Haziq; Rahman Al Azam; et al. (Malaysian Public Health Physicians Association, 2024)
Indexed by Scopus/MyCite